Controlling Nutritional Status (CONUT) Predicts Survival in Gastric Cancer Patients With Immune Checkpoint Inhibitor (PD-1/PD-L1) Outcomes - Chen, Li; Sun, Hao; Zhao, Ruihu; Huang, Rong; Pan, Hongming; Zuo, Yanjiao; Zhang, Lele; Xue, Yingwei; Song, Hongjiang; Li, Xingrui (Frontiers in Pharmacology, 2022)
Objective: The controlling nutritional status (CONUT), based on total lymphocyte count (TL), total cholesterol level (T-CHOL), and serum albumin (ALB), can provide a useful immunological prognostic biomarker for cancer patients. The present study aims to investigate the correlation between CONUT and prognosis in gastric cancer patients received immune checkpoint inhibitors (ICIs) treatment. Methods: We retrospectively enrolled 146 patients with gastric cancer treated with ICIs (PD-1 / PD-L1 inhibitors) from August 2016 to December 2020. The clinicopathologic characteristics were analyzed by Chi-square test or Fisher’s exact test. The Kaplan-Meier and Log-rank test were used to calculate and compare progression-free survival (PFS) and overall survival (OS). The prognostic and predictive factors of PFS and OS were identified by univariate and multivariate analyses. A nomogram was developed to estimate 1-, 3- and 5-year PFS and OS probability. Results: Through the CONUT score, there were 75 (51.37%) patients in low CONUT group, and 71 (48.63%) patients in high CONUT group. There was a correlation between the CONUT score and age (P=0.005), pathology (P=0.043), ALB (P=0.020), PALB (P=0.032), Hb (P=0.001). The CA724, TNM stage, treatment (ICIs vs Chemotherapy) were the independent prognostic factors for PFS and OS by multivariate analyses. Patients with high CONUT score had poorer PFS and OS (χ2=3.238, P=0.072 and χ2=4.298, P=0.038). In subgroup analysis, the patients with high CONUT score were associated with shorter PFS and OS with ICIs or Chemotherapy. With the PD-1 / PD-L1 positive expression, the patients with high CONUT score had survival shorter PFS and OS than those with low CONUT score. Furthermore, the patients with high CA724 value were associated with shorter PFS and OS. The toxicity assessment in ICIs or Chemotherapy, there was significantly associated with anemia. The nomograms were constructed to predict the probability of 1-, 3-, and 5-year PFS and 1-, 3-, 5-year OS with C-indexes of 0.749 and 0.769, respectively. Conclusions: The CONUT as a novel immuno-nutritional biomarker may be useful for identifying gastric cancer patients who are unlikely to benefit from ICIs treatment.